Mediastinal mass after a Blalock-Taussig shunt: utility of CT angiography. (2020)
Pseudoaneurysms are rare complications of Blalock-Taussig fistulas. We present the case of an abscessed right pulmonary aneurysm after a Blalock-Taussig fistula in the context of a Salmonella bacteremia.